Impaired early visual categorization of fear in social anxiety. (1st December 2019) - Meynadasy, Melissa; Clancy, Kevin; Ke, Zijun; Simon, Jessica; Wu, Wei; Li, Wen
Abstract: Social anxiety is associated with biased social perception, especially of ambiguous cues. While aberrations in high‐level processes (e.g., cognitive appraisal and interpretation) have been implicated in such biases, contributions of early, low‐level stimulus processing remain unclear. Categorical perception represents an efficient process to resolve signal ambiguity, and categorical emotion perception can swiftly classify sensory input, "tagging" biologically important stimuli at early stages of processing to facilitate ecological response. However, early threat categorization could be disrupted by exaggerated (or disinhibited) threat processing in anxiety, resulting in biased perception of ambiguous signals. We tested this hypothesis among individuals with low and high trait social anxiety (LSA/HSA; defined relative to the current sample), who performed a two‐alternative forced‐choice (fear or neutral) task on facial expressions parametrically varied along a neutral‐fear continuum. The groups diverged in the reaction time (RT) profile along the neutral‐fear continuum, which was characteristic of categorical perception in the LSA (vs. HSA) group with drastically increased RT from neutral to intermediate (boundary) fear intensities, contrasting monotonic, nonsignificant RT changes in the HSA group. Neurometric analysis along the continuum identified an early neutral‐fear categorization operation (arising in the P1, an early visual ERP at 100 ms), which was nonetheless impaired in the HSA group (due to disinhibited response at the neutral‐fear boundary). Absent group differences in higher‐level cognitive operations (identified by later ERPs), current findings highlight a dispositional cognitive vulnerability in early visual categorization of social threat, which could precipitate further cognitive aberrations and, eventually, the onset of social anxiety disorder. Abstract : Social anxiety disorder is a highly prevalent mental disorder. Biased social perception, especially of ambiguous cues, represents a key aspect of the psychopathology of social anxiety. While high‐level cognitive aberrations play a role in such biases, contributions of low‐level processes remain obscure. Combining psychophysical testing and neurometric analysis of ERPs to fearful expressions parametrically varied along a neutral‐fear continuum, we demonstrated that early perceptual categorization (at 100 ms), a process to resolve stimulus ambiguity, was impaired in social anxiety. Highlighting an early sensory mechanism in social perception, this study provides novel insights into the pathology of social anxiety.